LEARNING ENGLISH AS A FOREIGN LANGUAGE IN AN INDONESIAN UNIVERSITY: A STUDY OF NON-ENGLISH DEPARTMENT STUDENTS’ PREFERRED ACTIVITIES INSIDE AND OUTSIDE THE CLASSROOM - Urip Sulistiyo (IJET (Indonesian Journal of English Teaching), 2016)
This study examines a range of learning activities used in teaching English and identifies those that students see as most helpful. The instrument used in this study was a questionnaire adopted from Willing (1988). Some modification had been made to meet the purpose of this study. The questionnaire consists of two parts. Part 1 is ethnographic data in terms of the participants’ gender and field of study. Part 2 consists several items comprises students’ preferred activities in learning English. Students are asked to rank the activities of each category by circling one number. Circling number 1 means it is not helpful /preferable, while circling number 4 means it is very helpful /preferable for them. Then, all the responses were analyzed using SPSS Professional Statistics.The study suggests a number of pedagogical implication for English teaching and learning for non-English department students at universities in Indonesia. The finding suggests that teachers should take preferred activities into account when they are teaching. In addition, the study also proposed some suggestions for further research. These suggestions state the need to conduct research which involves more participants to confirm the results of the current study.